2022
DOI: 10.53819/81018102t2094
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Corporate Governance and Performance of Pension Fund Managers in Kenya

Abstract: Pension funds performance in Kenya have been facing myriad of challenges ranging from poor administration and investments of pension funds, lack of transparency and accountability, non-remittance of monthly contributions by employers, misappropriation of scheme assets by the trustees, loss of scheme funds through negligence of trustees and poor investment of the scheme assets. The objective of this study was to examine the relationships between corporate governance, and performance of registered pension fund m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…On the contrary, Goleman (1998) found that self-confident leaders have the strength to make difficult decisions and stand by their decisions despite disagreement or disapproval -demonstrated by a few principals who overturned decisions and/or made unpopular decisions. This level of selfconfidence may create hope, resilience, and optimism in colleagues, as Tanui et al (2018) argue.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Goleman (1998) found that self-confident leaders have the strength to make difficult decisions and stand by their decisions despite disagreement or disapproval -demonstrated by a few principals who overturned decisions and/or made unpopular decisions. This level of selfconfidence may create hope, resilience, and optimism in colleagues, as Tanui et al (2018) argue.…”
Section: Discussionmentioning
confidence: 99%